Immunogenetic characteristics of patients with autoimmune gastritis - Oksanen, Aino Mirjam; Haimila, Katri Eerika; Rautelin, Hilpi Iris Kaarina; Partanen, Jukka Antero (World journal of gastroenterology, 2010)
AIM: To explore whether predisposition to autoimmune gastritis (AIG) is found in human leukocyte antigen (HLA), cytokine or killer cell immunoglobulin-like receptor (KIR) gene variations. METHODS: Twelve Finnish patients with autoimmune-type severe atrophy of the gastric corpus were included. The patients' serum was analyzed for pepsinogen I and Helicobacter pylori (H. pylori) antibodies. DNA was separated and the patients were genotyped for HLA-A, B, Cw, DRB1 and DQB1 antigens, and studied for single nucleotide polymorphisms for the following cytokines: interleukin (IL)-1 gene cluster, IL-2, IL-4, IL-6, IL-10, IL-12, interferon gamma, transforming growth factor beta, and tumor necrosis factor alpha. Variation in KIR genes was also explored. The results were compared with prevalence of the polymorphisms in Finnish or European populations. RESULTS: All patients had pepsinogen I levels below normal (mean: 11 microg/L, range: < 5 to 25 microg/L). Three patients had elevated H. pylori IgG antibodies, while H. pylori serology was negative in the rest of the patients. AIG patients carried significantly more often HLA-DRB1*04 (58%) and DQB1*03 (83%) than the general Finnish population did (28% and 51%, respectively; P = 0.045 and 0.034 by the Fisher's exact test). No patient was positive for HLA-B8-DRB1*03, a well-established autoimmune marker. Neither cytokine polymorphisms nor KIR gene variation showed association with AIG. CONCLUSION: As explored with modern DNA-based methods, HLA-DRB1*04 and DQB1*03 alleles, but not HLA-B8-DRB1*03, may predispose to AIG.
Keywords: HLA-DRB1 řetězec; genetická predispozice k nemoci; Adult; autoimunitní nemoci; HLA-DRB1 Chains; HLA-DQ antigeny; membránové glykoproteiny; Male; lidé; Itálie; Genotype; lidé středního věku; Autoimmune Diseases; Humans; Gastritis; Polymorphism, Single Nucleotide; HLA-DQ beta-Chains; Middle Aged; Finland; jednonukleotidový polymorfismus; cytokiny; draslíkové kanály dovnitř usměrňující; Czech Republic; Cytokines; Membrane Glycoproteins; mužské pohlaví; Genetic Predisposition to Disease; Italy; Finsko; dospělí; HLA-DR Antigens; Potassium Channels, Inwardly Rectifying; Case-Control Studies; Česká republika; ženské pohlaví; gastritida; genotyp; Female; HLA-DQ beta řetězec; studie případů a kontrol; HLA-DR antigeny; HLA-DQ Antigens